Utilising one minute and four minute recovery when employing the resistance training contrast method does not negatively affect subsequent jump performance in the presence of concurrent training - Ritchie, Dean; Keogh, Justin W.L.; Reaburn, Peter; Bartlett, Jonathan D. (PeerJ, 2020)
Background Little is known about contrast training and post-activation performance enhancement (PAPE) in a same day concurrent training model. The aim of the current study was to examine the use of two short duration (1-min and 4-min) recovery periods on drop jump performance in same day concurrently trained athletes. Methods Ten professional Australian Rules footballers (age, 20.6 ± 1.9 yr; height, 184.8 ± 6.9 cm; body mass, 85.8 ± 8.4 kg) completed two resistance training sessions with different PAPE recovery durations; 1-min and 4-min, 1 h following a field-based endurance session. Baseline (pre) drop jumps were compared to post-test maximal drop jumps, performed after each set of three squats (where each participant was encouraged to lift as heavy as they could), to determine changes between 1-min and 4-min recovery periods. Data were analysed by fitting a mixed model (significance was set at P ≤ 0.05). Corrected Hedges’ g standardised effect sizes ±95% confidence limits were calculated using group means ± SDs. Results There were no significant differences between baseline and experimental sets 1, 2 and 3 for reactive strength index (RSI), flight time, and total and relative impulse for either recovery duration. However, for contact time, 1-min baseline was significantly different from set 2 (mean difference; 95% CI [0.029; 0.000–0.057 s], P = 0.047, ES; 95% CI [−0.27; −1.20 to 0.66]). For RSI and flight time, 1-min was significantly higher than 4-min (RSI: 0.367; 0.091 to 0.642, P = 0.010, ES; 95% CI [0.52; −0.37 to 1.42]; flight time: 0.033; 0.003 to 0.063 s, P = 0.027, ES; 95% CI [0.86; −0.06 to 1.78]). Discussion Short recovery periods of 1-min may be a time-efficient form of prescribing strength-power exercise in contrast loading schemes. Longer recovery periods do not appear to benefit immediate, subsequent performance.
Keywords: Training organisation; Periodisation; Team sport; Post-activation performance enhancement